Drug Delirium Scale (DDS): A Tool to Evaluate Drugs as a Risk Factor for Delirium - Viet-Quoc, Nguyen Patrick; Lucie, Pelletier; Isabelle, Payot; Judith, Latour (International Journal of Innovative Research in Medical Science, 2016)
Objectives: To design the Drug Delirium Scale (DDS), an evaluation tool to assess the drug burden in delirium in the elderly population. Design: We proceeded with a systematic literature review through database and grey literature. The records were examined by two independent reviewers using the inclusion and exclusion criteria. Data from the selected studies was extracted and a summary chart was written for each drug. Drugs in anticholinergic drug scales, Beers and STOPP criteria for anticholinergic of cognitive impairment effects were also included for evaluation. These summaries were submitted to the geriatric expert panel composed of two geriatric physicians and two geriatric pharmacists. The panel chose each drug included in the DDS list and their rank. Results: 981 records were identified and 149 met inclusion criteria. The expert panel evaluated 265 drugs and selected 96 drugs for the DDS scale. The mean interrater reliability score was of 0,634 [CI: 0,441; 0,791]. Conclusion: The Delirium Drug Scale (DDS) is the first evaluation tool to assess the risk of delirium derived from drugs used in the elderly population. It was designed using a sound methodological process. The DDS must now be tested in the geriatric population to validate its predictive value for delirium.